Limited ecoclinal variation found in Malva parviflora (small-flowered mallow) across the Mediterranean-climatic region of Western Australia - Michael, Pippa; Steadman, K.; Plummer, J. (CSIRO Publishing, 2006)
Malva parviflora populations were collected from 24 locations across the Mediterranean-climatic agricultural region of Western Australia and grown in Perth in a common garden experiment. Seventeen morphometric and taxonomic measurements were taken and genetic variation was investigated by performing principal components analysis (PCA). Taxonomic measurements confirmed that all plants used in the study were M. parviflora. Greater variation occurred within populations than between populations. Separation between populations was only evident between northern and southern populations along PC2, which was due mainly to flowering time. Flowering time and consequently photoperiod were highly correlated with latitude and regression analysis revealed a close relationship (r2 = 0.6). Additionally, the pollination system of M. parviflora was examined. Plants were able to self-pollinate without the need for external vectors and the pollen-ovule ratio (31 ± 1.3) revealed that M. parviflora is most likely to be an obligate inbreeder with a slight potential for outcrossing. The limited variation of M. parviflora enhances the likelihood of suitable control strategies being effective across a broad area.